Mobile Phones and Digital Library Services in Open and Distance Learning - Loveth Ogoeburan ,Ekwueme , Grace Ndukw Elem (IJoLIS, 2024)
Purpose: The study aims to provide an overview of concept and history of mobile phones and distance learning , characteristics digital libraries, and the applicationof mobile phones in libraries in open and distance learning(ODL).